A study on the behaviour of bituminous mixture with different fillers - Suhaimi bin Mahasan, Suhaimi (2009)
In this study, asphalt concrete specimens with 3 different types of fillers i. e. fly ash, lime and crumb tire rubber were studied by incorporating them in the bituminous mixture at the optimum bitumen content and were analyzed in the laboratory. This study found that there were improvement in the physical and mechanical properties of bituminous mixtures as a result of incorporating the different fillers.